Phylogenetic of sago palm (Metroxylon sagu) and others monocotyledon based on mitochondrial nad2 gene markers - Barahima Abbas; IHWAN TJOLLI; MUHAMMAD DAILAMI; MUNARTI (Society for Indonesian Biodiversity, 2019)
Abstract. Abbas B, Tjolli I, Dailami M, Munarti. 2019. Phylogenetic of sago palm (Metroxylon sagu) and others monocotyledon based on mitochondrial nad2 gene markers. Biodiversitas 20: 2249-2256. Sago palm forest and sago palm semi cultivated are found in the Papua islands as well as Ambon and Seram islands. The diversity center of sago palm is found in the Papua Islands. The objectives of this study are revealed sequence DNA mitochondrial associated with nad2 genes in sago palm accessions and molecular phylogenetic of sago palm and other monocotyledon plants. Plant materials used in the studies were derived from Sago Research Center (SRC) and sequencing and other monocotyledon were retrieved from the GenBank, NCBI accessions. Young fresh leaflets were derived from the experimental field of SRC and DNA extraction by following the procedure of Plant Genomic DNA Mini Kit and then PCR performed by using nad2 primer sets. Thereafter, DNA PCR product was sequenced by Macrogen Inc., Seoul, Korea. Sequences of nad2 genes in sago palm accessions from Papua, Indonesia were registered by GenBank NCBI for further used in the future as biological authenticity from the certain location. Mitochondrial DNA sequences associated with nad2 genes in the genome of sago palm were shown no differences among sago palm accessions. Molecular phylogenetic of sago palm and others monocotyledon based on nad2 gene markers showed the sago palm and others monocotyledon incorporated into two major clades and five subclades. Sago palm, coconut, and date palm were described as close related and being in the same subclades.